An Overview of Teilhard’s Commitment to ‘Seeing’ as Expressed in his Phenomenology, Metaphysics, and Mysticism - Grimes, John A. (Journal for the study of religion, nature and culture, 2005)
Using Teilhard’s emphasis on ‘seeing’ this article explores Teilhard de Chardin’s articulation of a vision of evolution as a dynamic process in which the psychic character of physical matter evolves into ever-greater complexity and consciousness. Teilhard proposed that evolutionary complexity-consciousness is especially evident in the appearance of humans. This work considers the significance of complexity-consciousness for Teilhard as an emergent property of a matter-spirit dialectic. This article investigates Teilhard’s commitment to seeing drawing on his phenomenology of an involution of matter, a metaphysics of union with spirit, and a mysticism of centration of person. Finally, there are brief considerations of the contributions and limits of Teilhard’s thought in light of contemporary issues.